René Girard and double bind theory of Palo Alto - Parrilla Martínez, Desiderio (Revista de Filosofía, 2015)
The term “double bind” was first used by anthropologist Gregory Bateson. René Girard takes this contribution from the School of Palo Alto to formulate his theory of “mimetic desire”. This paper presents the transformation of this notion in contemporary anthropology.
Keywords: René Girard; double bind; Palo Alto; mimetic desire; cybernetics.